High-wear-resistance anti-bending power cable and preparation method thereof
Through the combination of composite wood fiber material and polymer, the problem of insufficient wear resistance of the power cable sheath layer is solved, the balance of wear resistance and flexibility is achieved, and the stability of the cable is improved in complex environments.
Patent Information
- Application Number
- CN202510811580.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-18
- Publication Date
- 2025-07-22
- Estimated Expiration
- 2045-06-18
AI Technical Summary
The sheath layer of traditional power cables has poor wear resistance, and increasing wear-resistant filler will reduce the flexibility of the cable, resulting in uneven performance and affecting the stable operation of the cable under complex working conditions.
Compound ligno fiber materials are used to combine spherical yttrium oxide with ligno fiber powder and add vinylpyrrolidone-vinyl acetate copolymer to form composite ligno fibers, and combine them with polyvinyl chloride, polyethylene, methyl methacrylate-butadiene-styrene copolymer, etc. to improve the wear resistance of the sheath layer.
It significantly improves the wear resistance of the power cable sheath layer, while maintaining good flexibility and tensile performance, extending the service life of the cable and reducing wear.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of power cables, and specifically, to a highly wear-resistant and bend-resistant power cable and a preparation method thereof. Background Art
[0002] As an important carrier for power transmission, power cables are widely used in power systems, industrial equipment, building facilities, rail transit and other fields. With the continuous growth of power demand and the increasingly complex application environment, cables are often subjected to external forces such as mechanical stress, bending, and friction during laying and operation, which puts higher requirements on the performance of power cables.
[0003] Traditional power cables mostly use polyvinyl chloride and polyethylene as the basic materials for the insulating layer and the sheath layer. Although they have certain mechanical strength and electrical properties, in a long-term harsh environment, the surface of the cable is easily damaged due to wear, shortening the service life, and even causing potential safety hazards such as short circuits and electric leakage.
[0004] At present, to improve the wear resistance of the cable sheath layer, methods such as increasing the thickness of the sheath layer or adding wear-resistant fillers (such as carbon black, silica, etc.) are usually adopted. However, this method will reduce the flexibility of the cable, and at the same time, the excessive addition of wear-resistant fillers is likely to cause too large local performance differences in the cable sheath layer, which will instead limit the improvement of the wear resistance of the cable sheath layer.
[0005] Therefore, the research and development of a power cable that can significantly improve the wear resistance of the power cable sheath layer without a large amount of addition of wear-resistant fillers has extremely important practical significance for ensuring the long-term stable operation of power cables under complex working conditions. Summary of the Invention
[0006] The present invention provides a highly wear-resistant and bend-resistant power cable and a preparation method thereof, which solves the problem of poor wear resistance of the power cable sheath layer in the related art.
[0007] The technical solution of the present invention is as follows: The present invention provides a highly wear-resistant and bend-resistant power cable, which sequentially includes a sheath layer, an insulating layer and a conductor from outside to inside. The sheath layer includes the following components in parts by weight: 100 parts of polyvinyl chloride, 10 - 15 parts of high-density polyethylene, 4 - 8 parts of methyl methacrylate-butadiene-styrene copolymer, 15 - 20 parts of composite wood fiber, 0.5 - 1.5 parts of antioxidant, 2 - 3 parts of plasticizer; The raw materials of the composite wood fiber include wood fiber powder and spherical yttrium oxide in a weight ratio of 5 - 19:1; The raw materials of the composite wood fiber further include vinylpyrrolidone-vinyl acetate copolymer.
[0008] As a further technical solution, the weight ratio of the wood fiber powder to the spherical yttrium oxide is 9 to 17:1. For example, it can be 9:1, 10:1, 11:1, 12:1, 14:1, 16:1, 17:1, and preferably 9:1, 17:1.
[0009] In the present invention, when the weight ratio of the wood fiber powder to the spherical yttrium oxide is 9 to 17:1, the wear resistance of the power cable sheath layer can be further improved, and the wear quality of the power cable sheath layer is reduced to 0.087 to 0.092 g.
[0010] As a further technical solution, the preparation method of the composite wood fiber includes the following steps: B1. Add the spherical yttrium oxide into anhydrous ethanol and disperse it evenly to obtain a mixed solution I; B2. Add a silane coupling agent I and a surfactant I into anhydrous ethanol, mix them evenly to obtain a mixed solution II; B3. Add the mixed solution II into the mixed solution I, disperse it evenly, concentrate, and dry to obtain pretreated spherical yttrium oxide; B4. Add the pretreated spherical yttrium oxide, the vinylpyrrolidone-vinyl acetate copolymer, a silane coupling agent II, and a surfactant II into acetone. After dispersing them evenly, add the wood fiber powder, mix them evenly, concentrate, and dry to obtain the composite wood fiber.
[0011] As a further technical solution, the silane coupling agent I and the silane coupling agent II are each independently γ-mercaptopropyltrimethoxysilane; The surfactant I and the surfactant II are each independently oleic acid diethanolamide.
[0012] As a further technical solution, the weight ratio of the spherical yttrium oxide, the silane coupling agent I, and the surfactant I is 1:0.1 to 0.3:0.05 to 0.08. For example, it can be 1:0.1:0.05, 1:0.2:0.05, 1:0.3:0.05, 1:0.2:0.06, 1:0.2:0.08, 1:0.3:0.07, 1:0.3:0.08, and preferably 1:0.1:0.05, 1:0.3:0.08, and more preferably 1:0.3:0.08; The weight ratio of the wood fiber powder, the silane coupling agent II, and the surfactant II is 10:1 to 1.3:0.6 to 0.8. For example, it can be 10:1:0.6, 10:1.2:0.6, 10:1.3:0.6, 10:1:0.7, 10:1.2:0.7, 10:1.3:0.8, and preferably 10:1:0.6, 10:1.3:0.8, and more preferably 10:1.3:0.8.
[0013] In the present invention, both silane coupling agent I and silane coupling agent II are commonly used silane coupling agents in the art. For example, they can each independently be one or more of γ-mercaptopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, vinyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, and are preferably γ-mercaptopropyltrimethoxysilane; Both surfactant I and surfactant II are commonly used nonionic surfactants in the art. For example, they can each independently be one or more of oleic acid diethanolamide, coconut oil fatty acid diethanolamide, lauric acid diethanolamide, fatty alcohol polyoxyethylene ether, and are preferably oleic acid diethanolamide; The addition of silane coupling agent I can preliminarily organically modify the surface of spherical yttrium oxide, laying a foundation for the subsequent compounding of spherical yttrium oxide and wood fiber powder. Surfactant I can, to a certain extent, reduce the surface tension of the solution, improve the wettability and dispersibility of mixture II, thereby helping silane coupling agent I to better play its role on the surface of spherical yttrium oxide. By preliminarily treating spherical yttrium oxide with silane coupling agent I and surfactant I and reasonably controlling the weight ratio of spherical yttrium oxide, silane coupling agent I, and surfactant I, the success rate of the subsequent compounding of spherical yttrium oxide and wood fiber powder can be improved; In step B4, when silane coupling agent II, surfactant II, and pretreated spherical yttrium oxide are fully mixed, the secondary treatment of spherical yttrium oxide by the silane coupling agent and surfactant is achieved. After the secondary treatment, spherical yttrium oxide can be better combined with wood fiber powder, achieving the successful compounding of spherical yttrium oxide and wood fiber powder, thereby obtaining composite wood fiber.
[0014] As a further technical solution, in step B1, when it is uniformly dispersed, stir at 200 - 400 rpm for 10 - 20 min.
[0015] As a further technical solution, in step B3, when it is uniformly dispersed, stir at 200 - 400 rpm for 30 - 40 min at 50 - 60 °C.
[0016] As a further technical solution, in step B4, when it is uniformly dispersed, stir at 500 - 600 rpm for 40 - 60 min.
[0017] As a further technical solution, the weight ratio of the sum of the weights of the spherical yttrium oxide and the vinyl pyrrolidone-vinyl acetate copolymer to the weight of the wood fiber powder is 1:9; The weight ratio of the spherical yttrium oxide to the vinyl pyrrolidone-vinyl acetate copolymer is 1 - 3:1.
[0018] In the present invention, spherical yttrium oxide and wood fiber powder are used for composite treatment. Although the obtained composite wood fiber can improve the wear resistance of the sheath layer of the power cable, the dispersibility of the composite wood fiber in the matrix material is limited and agglomeration is likely to occur, which affects the tensile properties of the sheath layer of the power cable. When the raw materials of the composite wood fiber also include vinylpyrrolidone-vinyl acetate copolymer, the vinylpyrrolidone-vinyl acetate copolymer and spherical yttrium oxide are used to jointly conduct composite treatment on the wood fiber powder. While ensuring the wear resistance of the sheath layer of the power cable, the tensile properties of the sheath layer of the power cable can also be improved. And by reasonably adjusting the ratio relationship among spherical yttrium oxide, vinylpyrrolidone-vinyl acetate copolymer and wood fiber powder, when the weight ratio of the sum of the weights of spherical yttrium oxide and vinylpyrrolidone-vinyl acetate copolymer to the weight of wood fiber powder is 1:9 and the weight ratio of spherical yttrium oxide to vinylpyrrolidone-vinyl acetate copolymer is 1-3:1, the effect of improving the tensile properties of the sheath layer of the power cable can reach the optimum.
[0019] As a further technical solution, the antioxidant includes one or more of antioxidant 1010, antioxidant 300, and antioxidant 626.
[0020] As a further technical solution, the plasticizer includes one or two of dibutyl phthalate and dioctyl sebacate.
[0021] In the present invention, an antioxidant is added to the sheath layer of the power cable, which can capture free radicals and slow down the oxidative degradation of the organic matrix material, thereby improving the stability of the sheath layer material during processing and use. The antioxidant includes one or more of antioxidant 1010, antioxidant 300, and antioxidant 626, and preferably antioxidant 1010; The plasticizer is mainly used to weaken the intermolecular forces between the organic base material molecules of the sheath layer, making it easier to process and extrude, and reducing the processing energy consumption. The plasticizer includes one or two of dibutyl phthalate and dioctyl sebacate, and preferably dibutyl phthalate.
[0022] As a further technical solution, the material of the conductor is one of copper alloy and aluminum alloy; The insulating layer is a polyvinyl chloride insulating layer.
[0023] The present invention provides a method for preparing a highly wear-resistant and anti-bending power cable for preparing the highly wear-resistant and anti-bending power cable, including the following steps: S1. Extrude and coat the insulating layer around the conductor to form a cable semi-finished product; S2. After blending the components of the sheath layer, extrude and coat them on the surface of the cable semi-finished product to obtain the highly wear-resistant and anti-bending power cable.
[0024] The working principle and beneficial effects of the present invention are as follows: 1. In the present invention, the sheath layer of the power cable uses polyvinyl chloride as the matrix material, which provides the basic mechanical properties of the sheath layer. By adding high-density polyethylene, methyl methacrylate-butadiene-styrene copolymer, composite wood fiber, antioxidant, and plasticizer to the sheath layer, the synergistic effect of various component raw materials results in a power cable sheath layer with excellent wear resistance, thereby meeting the higher requirements for the wear resistance of the power cable.
[0025] 2. Polyvinyl chloride endows the sheath layer with basic mechanical properties, but polyvinyl chloride itself is relatively brittle. Introducing high-density polyethylene and acting together with polyvinyl chloride can, to a certain extent, improve the resilience of the power cable sheath layer, enabling the power cable to return to its original state after bending and reducing deformation; methyl methacrylate-butadiene-styrene copolymer is a core-shell structure elastomer. The butadiene segment can improve the flexibility of the power cable, and the methyl methacrylate and styrene segments can, to a certain extent, provide a rigid effect for the power cable. When rigidity and flexibility coexist, when the power cable is subjected to external friction, the presence of methyl methacrylate-butadiene-styrene copolymer in the sheath layer enables the power cable to not only resist the external stress brought by friction but also reduce the expansion of surface cracks, thereby reducing the wear degree of the power cable sheath layer.
[0026] 3. Composite wood fiber is introduced into the sheath layer of the power cable. The composite wood fiber is formed by compounding wood fiber powder and spherical yttrium oxide with a weight ratio of 5-19:1. Wood fiber powder and spherical yttrium oxide have a synergistic effect. When the composite wood fiber formed by their compounding is added to the sheath layer, it can have a good interfacial effect with the matrix material and can better transfer stress, thereby effectively improving the wear resistance of the power cable sheath layer. Specific embodiments
[0027] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts fall within the scope of protection of the present invention.
[0028] In the following examples and comparative examples, the type of polyvinyl chloride is NI00-50; the type of high-density polyethylene is DMDA-8008H; the type of methyl methacrylate-butadiene-styrene copolymer is TH-21B; the particle size of the wood fiber powder is 75 μm; the particle size of spherical yttrium oxide is 10 μm; the vinyl pyrrolidone-vinyl acetate copolymer, with CAS number 25086-89-9, is purchased from Wuhan Chengtian Fine Chemical Co., Ltd.; the material of the conductor is copper alloy, and the model is MF202.
[0029] Example 1 The preparation method of the composite wood fiber includes the following steps: A1. Add 2.5 parts of spherical yttrium oxide to 25 parts of absolute ethanol, stir at 200 rpm for 20 min, and disperse evenly to obtain mixture I; A2. Add 0.25 part of γ-mercaptopropyltrimethoxysilane and 0.125 part of diethanolamide oleate to 5 parts of absolute ethanol, mix evenly to obtain mixture II; A3. Add mixture II to mixture I, stir at 50 °C and 200 rpm for 40 min, disperse evenly, concentrate, and dry to obtain pretreated spherical yttrium oxide; A4. Add the above-mentioned pretreated spherical yttrium oxide, 1.25 parts of γ-mercaptopropyltrimethoxysilane, and 0.75 part of diethanolamide oleate to 25 parts of acetone, stir at 500 rpm for 60 min, after dispersing evenly, add 12.5 parts of wood fiber powder, mix evenly, concentrate, and dry to obtain composite wood fiber; A highly wear-resistant and bend-resistant power cable includes the following steps: S1. Extrude and coat the polyvinyl chloride insulating layer around the copper alloy conductor to form a cable semi-finished product; S2. After blending 100 parts of polyvinyl chloride, 10 parts of high-density polyethylene, 4 parts of methyl methacrylate-butadiene-styrene copolymer, 15 parts of the above-mentioned composite wood fiber, 0.5 part of antioxidant 1010, and 2 parts of dibutyl phthalate in the sheath layer, extrude and coat it on the surface of the cable semi-finished product to obtain a highly wear-resistant and bend-resistant power cable.
[0030] Example 2 The preparation method of the composite wood fiber includes the following steps: A1. Add 3 parts of spherical yttrium oxide to 25 parts of absolute ethanol, stir at 300 rpm for 15 min, and disperse evenly to obtain mixture I; A2. Add 0.9 part of γ-mercaptopropyltrimethoxysilane and 0.24 part of diethanolamide oleate to 5 parts of absolute ethanol, mix evenly to obtain mixture II; A3. Add the second mixture to the first mixture, stir at 300 rpm for 30 min at 60 °C until evenly dispersed, concentrate and dry to obtain pretreated spherical yttrium oxide; A4. Add the above pretreated spherical yttrium oxide, 1.95 parts of γ-mercaptopropyltrimethoxysilane and 1.2 parts of diethanolamide oleate to 25 parts of acetone, stir at 550 rpm for 50 min until evenly dispersed, then add 15 parts of wood fiber powder, mix evenly, concentrate and dry to obtain composite wood fiber; A highly wear-resistant and anti-bending power cable, comprising the following steps: S1. Extrude and coat a polyvinyl chloride insulation layer around the copper alloy conductor to form a cable semi-finished product; S2. After blending 100 parts of polyvinyl chloride, 13 parts of high-density polyethylene, 6 parts of methyl methacrylate-butadiene-styrene copolymer, 18 parts of the above composite wood fiber, 1 part of antioxidant 1010 and 2.5 parts of dibutyl phthalate in the sheath layer, extrude and coat it on the surface of the cable semi-finished product to obtain a highly wear-resistant and anti-bending power cable.
[0031] Example 3 The preparation method of the composite wood fiber comprises the following steps: A1. Add 1 part of spherical yttrium oxide to 25 parts of absolute ethanol, stir at 400 rpm for 10 min until evenly dispersed to obtain the first mixture; A2. Add 0.3 part of γ-mercaptopropyltrimethoxysilane and 0.08 part of diethanolamide oleate to 5 parts of absolute ethanol, mix evenly to obtain the second mixture; A3. Add the second mixture to the first mixture, stir at 400 rpm for 30 min at 60 °C until evenly dispersed, concentrate and dry to obtain pretreated spherical yttrium oxide; A4. Add the above pretreated spherical yttrium oxide, 2.47 parts of γ-mercaptopropyltrimethoxysilane and 1.52 parts of diethanolamide oleate to 25 parts of acetone, stir at 600 rpm for 40 min until evenly dispersed, then add 19 parts of wood fiber powder, mix evenly, concentrate and dry to obtain composite wood fiber; A highly wear-resistant and anti-bending power cable, comprising the following steps: S1. Extrude and coat a polyvinyl chloride insulation layer around the copper alloy conductor to form a cable semi-finished product; S2. After blending 100 parts of polyvinyl chloride, 15 parts of high-density polyethylene, 8 parts of methyl methacrylate-butadiene-styrene copolymer, 20 parts of the above composite wood fiber, 1.5 parts of antioxidant 1010 and 3 parts of dibutyl phthalate in the sheath layer, extrude and coat it on the surface of the cable semi-finished product to obtain a highly wear-resistant and anti-bending power cable.
[0032] Example 4 The difference between this embodiment and Embodiment 2 is only that in the preparation process of the composite wood fiber in this embodiment, 17.1 parts of wood fiber powder and 0.9 parts of spherical yttrium oxide are added.
[0033] Embodiment 5 The difference between this embodiment and Embodiment 2 is only that in the preparation process of the composite wood fiber in this embodiment, 16.2 parts of wood fiber powder and 1.8 parts of spherical yttrium oxide are added.
[0034] Embodiment 6 The difference between this embodiment and Embodiment 2 is only that in the preparation process of the composite wood fiber in this embodiment, 17 parts of wood fiber powder and 1 part of spherical yttrium oxide are added.
[0035] Embodiment 7 The difference between this embodiment and Embodiment 5 is only that the preparation process of the composite wood fiber in this embodiment is different, specifically as follows: B1. Add 0.5 part of spherical yttrium oxide to 25 parts of absolute ethanol, stir at 300 rpm for 15 min to disperse evenly, and obtain mixture I; B2. Add 0.9 part of γ-mercaptopropyltrimethoxysilane and 0.24 part of diethanolamide oleate to 5 parts of absolute ethanol, mix evenly, and obtain mixture II; B3. Add mixture II to mixture I, stir at 300 rpm at 60 °C for 30 min to disperse evenly, concentrate, and dry to obtain pretreated spherical yttrium oxide; B4. Add the above pretreated spherical yttrium oxide, 1.3 parts of vinyl pyrrolidone-vinyl acetate copolymer, 1.95 parts of γ-mercaptopropyltrimethoxysilane, and 1.2 parts of diethanolamide oleate to 25 parts of acetone, stir at 550 rpm for 50 min to disperse evenly, then add 16.2 parts of wood fiber powder, mix evenly, concentrate, and dry to obtain composite wood fiber.
[0036] Embodiment 8 The difference between this embodiment and Embodiment 7 is only that in the preparation process of the composite wood fiber in this embodiment, 1.5 parts of spherical yttrium oxide and 0.3 part of vinyl pyrrolidone-vinyl acetate copolymer are added.
[0037] Embodiment 9 The difference between this embodiment and Embodiment 7 is only that in the preparation process of the composite wood fiber in this embodiment, 0.9 part of spherical yttrium oxide and 0.9 part of vinyl pyrrolidone-vinyl acetate copolymer are added.
[0038] Embodiment 10 The difference between this embodiment and Embodiment 7 is only that, in the preparation process of the composite wood fiber in this embodiment, 1.35 parts of spherical yttrium oxide and 0.45 parts of vinylpyrrolidone-vinyl acetate copolymer are added.
[0039] Comparative Example 1 The difference between this comparative example and Embodiment 2 is only that, in this comparative example, the composite wood fiber is replaced with an equal amount of wood fiber powder.
[0040] Comparative Example 2 The difference between this comparative example and Embodiment 2 is only that, in this comparative example, the composite wood fiber is replaced with an equal amount of spherical yttrium oxide.
[0041] Comparative Example 3 The difference between this comparative example and Embodiment 2 is only that, in this comparative example, no composite wood fiber is added.
[0042] Comparative Example 4 The difference between this comparative example and Embodiment 1 is only that, in the preparation process of the composite wood fiber in this comparative example, the spherical yttrium oxide is replaced with spherical alumina.
[0043] Comparative Example 5 The difference between this comparative example and Embodiment 5 is only that, in this embodiment, the preparation process of the composite wood fiber is different, specifically: 1.8 parts of vinylpyrrolidone-vinyl acetate copolymer, 1.95 parts of γ-mercaptopropyltrimethoxysilane, and 1.2 parts of diethanolamide oleate are added to 25 parts of acetone, stirred at 550 rpm for 50 min, after being dispersed evenly, 16.2 parts of wood fiber powder are added, mixed evenly, concentrated, and dried to obtain the composite wood fiber.
[0044] Experimental Example 1 The sheath layers of the power cables prepared in Embodiments 1 to 10 and Comparative Examples 1 to 5 were subjected to mass wear testing using the measurement method in GB / T 3960-2016 "Test Method for Plastic Sliding Friction and Wear", and the test results are shown in Table 1.
[0045] Table 1 Volume Wear Test Results of Sheath Layer
[0046] Compared with Comparative Examples 1 to 5, the mass wear of the sheath layer of the power cables prepared in Embodiments 1 to 10 can be reduced to 0.125 g, indicating that when the composite wood fiber obtained by composite treatment with spherical yttrium oxide, vinylpyrrolidone-vinyl acetate copolymer, and wood fiber powder is added to the power cable sheath layer, the wear resistance of the power cable sheath layer can be significantly improved.
[0047] Experimental Example 2 Three specimens were cut from the sheath layers of the power cables prepared in Example 5, Examples 7 to 10, and Comparative Example 5, and dumbbell specimens with a thickness of 2 mm were prepared according to the method in GB / T 2951.11-2008 "General test methods for insulating and sheathing materials of cables and optical cables - Part 11: General test methods - Measurement of thickness and overall dimensions, Mechanical properties test", and the tensile strength was tested. The test results are shown in Table 2.
[0048] Table 2 Tensile strength test results of the sheath layer
[0049] Compared with Example 5 and Comparative Example 5, the tensile strength of the sheath layer of the power cables prepared in Examples 7 to 10 is improved, indicating that when vinylpyrrolidone-vinyl acetate copolymer is introduced into the raw materials of the composite wood fiber, the tensile strength of the sheath layer of the power cable can be improved by using vinylpyrrolidone-vinyl acetate copolymer and spherical yttrium oxide to jointly perform composite treatment on the wood fiber powder.
[0050] The 360-degree bending test machine (model HH-8618A) was used to conduct a swing experiment on the bending resistance performance of the power cables prepared in Examples 1 to 3. After swinging 5000 times at a swing speed of 30 times / min under an applied external force of 5 N, the power cable specimens did not break and no cracks were generated on the surface, indicating that the power cable provided by the present invention has good bending resistance performance.
[0051] The above are only the preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A highly wear-resistant and bend-resistant power cable, which sequentially includes a sheath layer, an insulating layer, and a conductor from outside to inside, is characterized in that The sheath layer comprises the following components in parts by weight: 100 parts of polyvinyl chloride, 10 - 15 parts of high-density polyethylene, 4 - 8 parts of methyl methacrylate-butadiene-styrene copolymer, 15 - 20 parts of composite wood fiber, 0.5 - 1.5 parts of antioxidant, 2 - 3 parts of plasticizer; The raw materials of the composite wood fiber include wood fiber powder and spherical yttrium oxide in a weight ratio of 5 - 19:1; The raw materials of the composite wood fiber further include vinyl pyrrolidone-vinyl acetate copolymer.
2. The highly wear-resistant and anti-bending power cable according to claim 1, wherein The weight ratio of the wood fiber powder to the spherical yttrium oxide is 9 - 17:
1.
3. A highly wear-resistant and anti-bending power cable according to claim 1, characterized in that, The preparation method of the composite wood fiber comprises the following steps: B1. Add spherical yttrium oxide into absolute ethanol, disperse evenly to obtain mixture I; B2. Add silane coupling agent I and surfactant I into absolute ethanol, mix evenly to obtain mixture II; B3. Add the mixture II into the mixture I, disperse evenly, concentrate, and dry to obtain pretreated spherical yttrium oxide; B4. Add the pretreated spherical yttrium oxide, the vinyl pyrrolidone-vinyl acetate copolymer, silane coupling agent II, and surfactant II into acetone, disperse evenly, then add the wood fiber powder, mix evenly, concentrate, and dry to obtain composite wood fiber.
4. The highly wear-resistant and bend-resistant power cable according to claim 3, wherein, The silane coupling agent I and the silane coupling agent II are each independently γ-mercaptopropyltrimethoxysilane; The surfactant I and the surfactant II are each independently oleic acid diethanolamide.
5. A highly wear-resistant and bend-resistant power cable according to claim 3, characterized in that, The weight ratio of the spherical yttrium oxide, silane coupling agent I, and surfactant I is 1:0.1 - 0.3:0.05 - 0.08; The weight ratio of the wood fiber powder, silane coupling agent II, and surfactant II is 10:1 - 1.3:0.6 - 0.
8.
6. A highly wear-resistant and anti-bending power cable according to claim 1, characterized in that, The weight sum of the spherical yttrium oxide and the vinyl pyrrolidone-vinyl acetate copolymer and the weight ratio of the wood fiber powder is 1:9; The weight ratio of the spherical yttrium oxide to the vinyl pyrrolidone-vinyl acetate copolymer is 1 - 3:
1.
7. A highly wear-resistant and anti-bending power cable according to claim 1, characterized in that, The antioxidant includes one or more of antioxidant 1010, antioxidant 300, and antioxidant 626.
8. The highly wear-resistant and anti-bending power cable according to claim 1, characterized in that, The plasticizer includes one or two of dibutyl phthalate and dioctyl sebacate.
9. The high-wear-resistant and anti-bending power cable according to claim 1, characterized in that, The material of the conductor is one of copper alloy and aluminum alloy; The insulating layer is a polyvinyl chloride insulating layer.
10. A preparation method of a highly wear-resistant and anti-bending power cable, which is used to prepare a highly wear-resistant and anti-bending power cable according to any one of claims 1 to 9, characterized in that, Comprises the following steps: S1. Extrude and coat the insulating layer around the conductor to form a cable semi-finished product; S2. After blending the components of the sheath layer, extrude and coat it on the surface of the cable semi-finished product to obtain the high-wear-resistant and anti-bending power cable.
Citation Information
Patent Citations
High-performance wire / cable protection tube material and preparation method thereof
CN108727799A
Flame-retardant insulated cable
CN118562225A
Tensile new energy charging pile cable
CN119661949A
Biodegradable plastic composition
EP4377394A1
Cable and process for manufacturing the same
WO2007135489A1